Proceedings of the 39th IEEE Conference on Decision and Control (Cat. No.00CH37187)
DOI: 10.1109/cdc.2000.912124
|View full text |Cite
|
Sign up to set email alerts
|

Classification of electrocardiographic p-wave morphology

Abstract: Abstract-The atrial activity of the human heart is normally visible in the electrocardiogram as a P-wave. In patients with intermittent atrial fibrillation, a different P-wave morphology can sometimes be seen, indicating atrial conduction defects. The purpose of this study was to develop a method to discriminate between such P-waves and normal ones. 20 recordings of each type were used in a classification which, based on impulse response analysis of the P-wave and linear discrimination between various paramete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 13 publications
0
16
0
Order By: Relevance
“…Over recent years filtered techniques of P-wave signal averaging have been most extensively studied. Their combination with unfiltered P-wave analysis seems, however, perspective in identifying concealed conduction defects which are of importance for AF inducibility and sustenance [58,67]. Analysis of unfiltered P-waves identified two features to be characteristic for lone AF: (1) double-peaked P-wave morphology in spatial magnitude and (2) biphasic P-waves in the Z-lead [58,67].…”
Section: P-wave Signal Averaged Ecgmentioning
confidence: 94%
“…Over recent years filtered techniques of P-wave signal averaging have been most extensively studied. Their combination with unfiltered P-wave analysis seems, however, perspective in identifying concealed conduction defects which are of importance for AF inducibility and sustenance [58,67]. Analysis of unfiltered P-waves identified two features to be characteristic for lone AF: (1) double-peaked P-wave morphology in spatial magnitude and (2) biphasic P-waves in the Z-lead [58,67].…”
Section: P-wave Signal Averaged Ecgmentioning
confidence: 94%
“…Changes in P-wave polarity as well as subtle differences in P-wave morphology are believed to reflect abnormal activation patterns in the atria [3] [4]. Irregularities in the orthogonal P-wave morphology have been detected in AF patients and associated with local inter-atrial conduction delay [2].…”
Section: Introductionmentioning
confidence: 99%
“…Irregularities in the orthogonal P-wave morphology have been detected in AF patients and associated with local inter-atrial conduction delay [2]. Different shapes of P-wave have been shown to represent the presence or absence of an underlying pathophysiological condition in patients prone to AF attacks [4]. In the presence of a partial inter-atrial conduction block, P-wave shape changes have been demonstrated to depend on the direction of the activation wavefront [5].…”
Section: Introductionmentioning
confidence: 99%
“…Low variance is a strong indicator for sudden cardiac failure. The second common digital signal processing medical application is classifying heartbeats as either normal or associated with a cardiac malady (Kundu et al, 2000;Vila et al, 2000;Carlson et al, 2001). This latter process is an application of supervised classification.…”
Section: Introductionmentioning
confidence: 99%